The influence of maternal body mass index and physical activity on select cardiovascular risk factors of preadolescent Hispanic children - Basil A. Alhassan; Ying Liu; Deborah Slawson; Jonathan M. Peterson; Jo-Ann Marrs; William A. Clark; Arsham Alamian (PeerJ, 2018)
Background Maternal obesity and physical inactivity have been identified as correlates of overweight and obesity and physical inactivity in older preadolescents; however, no study has explored this relationship in Hispanic preadolescents. Furthermore, the relation between maternal physical activity (PA) and blood pressure (BP) in Hispanic preadolescents has not been examined. Purpose This study aimed to assess the associations between Hispanic mothers’ PA and body mass index (BMI) and their preadolescents’ PA, screen time, BP, and BMI. Methods Data of 118 mother-child (aged 2–10 years) dyads enrolled in a cross-sectional study of metabolic syndrome in Hispanic preadolescents at a community health center in Johnson City, TN were used. Parent and child questionnaires were used to ascertain mothers’ BMI and PA and preadolescents’ PA and screen time. Preadolescents’ height, weight, and BP were measured. Multiple logistic regression was used to examine the association between child and maternal variables, adjusting for mother’s education and the child’s sex and age. Results Pradolescents of obese mothers were more likely than preadolescents of mothers with normal weight to engage in less than three days of at least 60 min of vigorous PA per week (OR: 6.47, 95% CI [1.61–26.0]). Preadolescents whose mothers did not engage in moderate PA were more likely to engage in less than three days of at least 60 min of vigorous PA per week (OR: 2.92, CI [1.18–7.24]); and have elevated BP (OR: 2.50, 95% CI [1.02–4.53]) than preadolescents whose mothers engaged in moderate PA. Discussion Our results show a negative relationship between maternal obesity and preadolescent PA, and a positive relationship between lower maternal PA and elevated BP and lower PA in Hispanic preadolescents. This suggests that interventions aimed at improving Hispanic preadolescents’ PA and BP may use maternal PA and maternal BMI (for preadolescent PA) as a modification strategy to improve health in Hispanic preadolescents.